Vietnamese Driving Curricula from 1998 to 2023: A Review - Nguyễn Xuân Trung (Journal of Technical Education Science, 2024)
From 1998 to 2023, our country’s driving curricula have undergone nine instances of new enactments or revisions. However, no research on the development of driving curricula has been published by state management agencies. This article analyzes and evaluates the changes in automobile driving training programs over time, focusing on objectives, structure, and implementation. Additionally, these changes are compared with relevant legal regulations, particularly those pertaining to vocational education, of which driving training is a component. The findings reveal that driving training goals are hardly set, the training curricula have outdated structures, many internal shortcomings, and lack continuity and succession. Furthermore, the regulations for program implementation are illogical, lack a scientific basis, and are inappropriate for vocational education. Therefore, in the context of changing road traffic laws, it is necessary to soon rebuild car driver training programs, methods, and content of driving license testing, as well as the periodic evaluation and accreditation of training and testing quality.